2013
DOI: 10.1088/0264-9381/30/23/235007
|View full text |Cite
|
Sign up to set email alerts
|

What happens at the horizon(s) of an extreme black hole?

Abstract: A massless scalar field exhibits an instability at the event horizon of an extreme black hole. We study numerically the nonlinear evolution of this instability for spherically symmetric perturbations of an extreme Reissner-Nordstrom (RN) black hole. We find that generically the endpoint of the instability is a non-extreme RN solution. However, there exist fine-tuned initial perturbations for which the instability never decays. In this case, the perturbed spacetime describes a time-dependent extreme black hole.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 49 publications
(202 reference statements)
8
116
0
Order By: Relevance
“…However, it turns out that an exactly extremal black hole behaves quite differently from a near-extremal black hole. For example, an (exactly) extremal black hole suffers from the -classical -Aretakis instability but near-extremal ones do not [23][24][25][26][27][28][29]. Furthermore, the procedure of taking the extremal limit is quite subtle [30][31][32].…”
Section: Black Holes and Their Photon Orbitsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it turns out that an exactly extremal black hole behaves quite differently from a near-extremal black hole. For example, an (exactly) extremal black hole suffers from the -classical -Aretakis instability but near-extremal ones do not [23][24][25][26][27][28][29]. Furthermore, the procedure of taking the extremal limit is quite subtle [30][31][32].…”
Section: Black Holes and Their Photon Orbitsmentioning
confidence: 99%
“…In fact, the instability of the photon orbit for Kerr black holes outside their horizon was a crucial ingredient used in the proof that slowly rotating Kerr black holes are stable when considering linear wave equation on the background [80]. The fact that static extremal black holes have stable photon orbits, on the contrary, implies that these black holes are unstable (even without considering the Aretakis instability [23][24][25][26][27][28][29]). The question is then: what exactly happens to the geometry due to this backreaction?…”
Section: Conclusion: Light On the Event Horizon Of Extremal Black Holesmentioning
confidence: 99%
“…They found that for fine-tuned initial data the corresponding future developments are black hole spacetimes containing no (marginally) trapped surfaces of symmetry that approach extremal Reissner-Nordström along the event horizon. 5 Moreover, the numerics in [42] suggest that the interior region of these spacetimes has a non-empty Cauchy horizon across which the metric is extendible in C 0 with Christoffel symbols in L 2 loc at the Cauchy horizon. Additionally, both the scalar field φ and all its first-order derivatives remain bounded at the Cauchy horizon.…”
Section: Results For the Spherically Symmetric Einstein-maxwell-scalamentioning
confidence: 97%
“…(Furthermore, note that the quantity M − e 2 r is always positive in R.) As defined in (35) the r coordinate in the noshift region N ranges between r red defined by (36) and r blue , defined below, strictly bigger than r − . In N we exploit the fact that J −∂ r and K −∂ r are invariant under translations along ∂ t .…”
Section: Eddington-finkelstein Coordinatesmentioning
confidence: 99%